Acceptability and usability of a patient portal for men with prostate cancer in follow-up care - O’Connor, David; Frankland, Jane; Watts, Jo; Brodie, Hazel; Hamer, Kevin; Foster, Claire; Richardson, Alison (Frontiers in Digital Health, 2022)
Background: A stratified approach to cancer follow-up care, including remote monitoring and supported self-management for suitable patients, is increasingly recommended. Patient portals can facilitate such an approach, allowing access to results and information. There is limited understanding of the use of portals within this context. Aim: This paper reports the acceptability and useability of a patient portal developed to facilitate a remote monitoring and supported self-management follow-up care programme for men with prostate cancer. Methods: A mixed methods evaluation, including analysis of service utilisation data, a survey of users’ experiences and satisfaction, and telephone interviews of non-users’ views and experiences. Results: Sixty percent of eligible patients registered to use the portal. Of these, 37% logged in at least once over a 6-month period and 52% over 12 months. Satisfaction among these users was reasonably high. Use of the portal in general was rated as very easy or easy by over 70% of respondents, and the majority felt the portal had helped them manage their condition in various ways. However, a large minority (40%) did not use the portal, with reasons for non-use including lack of access to computing facilities and lack of computer skills. Those who were older were less likely to register to use the portal. Conclusions: A large proportion of participants found the patient portal acceptable and easy to use. Reasons for non-use should be addressed in order to maximise system efficiencies and minimise inequalities in care, and the needs of specific groups should be taken into account.